2010
DOI: 10.1590/s0100-204x2010001000005
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e reprodução da mariposa-oriental em macieira e pessegueiro

Abstract: Resumo -O objetivo deste trabalho foi avaliar o desenvolvimento de estágios imaturos e parâmetros reprodutivos de adultos de Grapholita molesta em dietas naturais, constituídas de ramos e frutos de pessegueiro 'Vanguarda', frutos de macieira 'Gala' e 'Fuji', e em dieta artificial à base de milho. O delineamento experimental foi inteiramente casualizado. Considerou-se cada inseto uma repetição e, no estudo dos parâmetros biológicos dos adultos, cada casal foi considerado uma repetição. Foi calculada a tabela de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 10 publications
(15 reference statements)
2
17
2
Order By: Relevance
“…The observed values (211.1 Ϯ 5.90, 290.0 Ϯ 9.70, and 313.0 Ϯ 6.65 eggs for insects reared on the artiÞcial diet, Fuji apples, and burrknots, respectively) are higher than those reported by Silva et al (2010), who reared this insect on branches and fruits of peaches and apples, and obtained a mean fertility ranging from 110 to 202 eggs.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The observed values (211.1 Ϯ 5.90, 290.0 Ϯ 9.70, and 313.0 Ϯ 6.65 eggs for insects reared on the artiÞcial diet, Fuji apples, and burrknots, respectively) are higher than those reported by Silva et al (2010), who reared this insect on branches and fruits of peaches and apples, and obtained a mean fertility ranging from 110 to 202 eggs.…”
Section: Discussionmentioning
confidence: 56%
“…These periods are similar to the 3.07 d reported by Grellmann et al (1991), who studied the embryonic development at 26ЊC. For the larval stage, the longest duration observed for insects fed on burrknots (19.1 d) in relation to apples (15.9 d) and artiÞcial diet (14.8 d), is greater than the values reported for preferred hosts, such as branches (13.0 d) and fruits (14.0 d) of peach trees (Silva et al 2010). However, Rosenthal et al (1994), using the same artiÞcial diet and temperature, found a duration of 20.5 d for larval development of G. molesta.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations